Flavonoids of the genus Annona / Flavonoides do Gênero Annona - Anderson Soares de Almeida; Aldenir Feitosa dos Santos () (Universidade Estadual de Alagoas, 2018)
Widely distributed in Central America, South Africa and Asia, the Annonaceae family is made up of about 130 genera and 2,300 species. Among the genus of this family stands out the genus Annona, constituted of 118 species where 13 are producers of edible fruits. Plants of this genus have significant importance in the discovery of new drugs and cosmetics. Chemotaxonomy is an area of botany that uses chemical data in solving taxonomic problems. The present study aimed to identify groups of flavonoids of species in the genus Annona. A review of the literature in the Google Academic and Scielo databases on works published between 2000 and 2017, with the keywords - flavonoids, genus Annona, 2,245 articles were retrieved, which by the analysis of the title \ abstract was selected 05 papers. The study allowed to catalog 25 substances, being 24 flavonols, 3 flavanols and 1 flavone. Therefore, flavonols can be considered as one of the chemical markers of the genus Annona.